2018
DOI: 10.15252/embj.2018100101
|View full text |Cite
|
Sign up to set email alerts
|

A pathogenic role for cystic fibrosis transmembrane conductance regulator in celiac disease

Abstract: Intestinal handling of dietary proteins usually prevents local inflammatory and immune responses and promotes oral tolerance. However, in ~ 1% of the world population, gluten proteins from wheat and related cereals trigger an HLA DQ2/8‐restricted TH1 immune and antibody response leading to celiac disease. Prior epithelial stress and innate immune activation are essential for breaking oral tolerance to the gluten component gliadin. How gliadin subverts host intestinal mucosal defenses remains elusive. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
116
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(121 citation statements)
references
References 84 publications
3
116
0
Order By: Relevance
“…The adaptive immune response causes epithelial cell stress, which promotes recruitment of invariant natural killer T (NKT) cells to the intestinal epithelium; this is believed to be a major driver of tissue destruction in CD. Here, Villella et al () discovered a new likely key cause of intestinal cell stress and destruction due to inhibition of CFTR expression and function by gliadin peptides.…”
Section: Interaction Of the Gliadin Peptide P31‐43 And Vx‐770 With Cftrmentioning
confidence: 99%
See 4 more Smart Citations
“…The adaptive immune response causes epithelial cell stress, which promotes recruitment of invariant natural killer T (NKT) cells to the intestinal epithelium; this is believed to be a major driver of tissue destruction in CD. Here, Villella et al () discovered a new likely key cause of intestinal cell stress and destruction due to inhibition of CFTR expression and function by gliadin peptides.…”
Section: Interaction Of the Gliadin Peptide P31‐43 And Vx‐770 With Cftrmentioning
confidence: 99%
“…Based on several similar intestinal symptoms in CD and CF, Villella et al () reasoned that aberrant intestinal CFTR function might occur in CD, and if it does, it might be corrected by CFTR potentiators. Indeed, Villella et al found that gliadin administration triggers inflammatory response in CFTR −/− mice.…”
Section: Interaction Of the Gliadin Peptide P31‐43 And Vx‐770 With Cftrmentioning
confidence: 99%
See 3 more Smart Citations